Analisa Pendapatan Usahatani Tanaman Pacar Air di Desa Dukuh Klopo Kecamatan Peterongan Kabupaten Jombang - Viki Rahmatullah; Dyah Ayu Sri Hartanti; Siti Nur Qomariyah (University of Islam Malang, 2021)
Agriculture is a significant sector of the Indonesian economy. Farmers strive for economically advantageous outcomes in the processing of farming, where the costs paid can result in maximum production. This increases demand for flowers, one of which is water henna. Farmers must enhance production to fulfill the demand for water henna flowers. The purpose of this study is to determine the viability of water henna flower growing in Dukuh Klopo Village, Peterongan District, Jombang Regency. The analytical method employed in this research is a combination of descriptive and quantitative analysis, which will be used to determine the income generated by water henna farming. According to the feasibility analysis results, the B/C – Ratio for water henna plant cultivation in Dukuh Klopo Village, Peterongan District, Jombang Regency is 1.57. This means that for every Rp. 1 spent, the henna plant farming industry in Dukuh Klopo Village, Peterongan District, Jombang Regency generates Rp. 1.57 rupiah in revenue. Thus, the B/C Ratio approach enables the development of water henna flower farming in Dukuh Klopo Village, Peterongan District, Jombang Regency.